Wood : materials for inspirational design. - Lefteri, Chris, ....- (Mies : Rotovision, 2005)
This fabulously illustrated book offers a rich and unique introduction to wood. A range of projects, products, and processes are featured to demonstrate some of the extraordinary possibilities of wood and to challenge the boundaries of traditional applications. It includes everyday, familiar, and iconic products, along with those that are new, exciting and unexpected. Applications covered include architecture, interior design, product design, furniture design and more. Each product is introduced with authorial comment, interviews with the designers and manufacturers, and solid technical information, making this a uniquely attractive and practical book for designers.
Keywords: Hout; Industrieel ontwerpen